Virological failure and antiretroviral resistance among HIV-infected children after five years follow-up in the ANRS 12225-PEDIACAM cohort in Cameroon - Tagnouokam-Ngoupo, Paul Alain (PLoS One, 2021)
OBJECTIVE: In the present study, we aimed to evaluate the virological failure (VF) and drug resistance among treated HIV-infected children after five years follow-up in the ANRS-Pediacam cohort in Cameroon. METHODS: From November 2007 to October 2011, HIV-infected children born to HIV-infected mothers were included in the ANRS-PEDIACAM study and followed-up for more than 5 years. Plasma viral load (VL) was measured at each visit (every three months until month 24 and every 6 months thereafter). VF was the main outcome and HIV drug resistance test was performed using the ANRS procedures and algorithm. RESULTS: Data from 155 children were analyzed. The median age at combination antiretroviral therapy (cART) initiation was 4.2 months (interquartile range (IQR): 3.2–5.8), with 103 (66.5%) children taking LPV/r-containing regimen and 51 (32.9%) children taking NVP. After five years follow-up, 63 (40.6%; CI: 32.9–48.8) children experienced VF. The median duration between cART initiation and VF was 22.1 months (IQR: 11.9–37.1) with a median VL of 4.8 log10 (IQR: 4.0–5.5). Among the 57 children with HIV drug resistance results, 40 (70.2%) had at least one drug resistance mutation. The highest resistance rates (30.4–66.1%) were obtained with Lamivudine; Efavirenz; Nevirapine and Rilpivirine. CONCLUSIONS: These results show high resistance to NNRTI and emphasize the need of VL and resistance tests for optimal follow-up of HIV-infected people especially children.